Cancer cachexia causes skeletal muscle damage via transient receptor potential vanilloid 2‐independent mechanisms, unlike muscular dystrophy. Issue 3 (19th November 2015) - Iwata, Yuko; Suzuki, Nobuyuki; Ohtake, Hitomi; Kamauchi, Shinya; Hashimoto, Naohiro; Kiyono, Tohru; Wakabayashi, Shigeo
Abstract: Background: Muscle wasting during cancer cachexia contributes to patient morbidity. Cachexia‐induced muscle damage may be understood by comparing its symptoms with those of other skeletal muscle diseases, but currently available data are limited. Methods: We modelled cancer cachexia in mice bearing Lewis lung carcinoma/colon adenocarcinoma and compared the associated muscle damage with that in a murine muscular dystrophy model ( mdx mice). We measured biochemical and immunochemical parameters: amounts/localization of cytoskeletal proteins and/or Ca 2+ signalling proteins related to muscle function and abnormality. We analysed intracellular Ca 2+ mobilization and compared results between the two models. Involvement of Ca 2+ ‐permeable channel transient receptor potential vanilloid 2 (TRPV2) was examined by inoculating Lewis lung carcinoma cells into transgenic mice expressing dominant‐negative TRPV2. Results: Tumourigenesis caused loss of body and skeletal muscle weight and reduced muscle force and locomotor activity. Similar to mdx mice, cachexia muscles exhibited myolysis, reduced sarcolemmal sialic acid content, and enhanced lysosomal exocytosis and sarcolemmal localization of phosphorylated Ca 2+ /CaMKII. Abnormal autophagy and degradation of dystrophin also occurred. Unlike mdx muscles, cachexia muscles did not exhibit regeneration markers (centrally nucleated fibres), and levels of autophagic proteolytic pathway markers increased. While a slight accumulation of TRPV2 was observed in cachexia muscles, Ca 2+ influx via TRPV2 was not elevated in cachexia‐associated myotubes, and the course of cachexia pathology was not ameliorated by dominant‐negative inhibition of TRPV2. Conclusions: Thus, cancer cachexia may induce muscle damage through TRPV2‐independent mechanisms distinct from those in muscular dystrophy; this may help treat patients with tumour‐induced muscle wasting.